Impact of skier actions on the gliding times in alpine skiing - Federolf, P.; Scheiber, P.; Rauscher, E.; Schwameder, H.; Lüthi, A.; Rhyner, H.-U.; Müller, E. (Scandinavian Journal of Medicine & Science in Sports, 2008)
Alpine ski races are typically won by fractions of a second. It is therefore essential for ski racers to minimize air drag as well as ski-snow friction. In contrast to air drag, ski-snow friction during actual skiing has rarely been investigated so far. Two tasks, forward/backward leaning and edging of the skis, were selected, which (a) were expected to have an impact on ski-snow friction, and (b) could be executed while gliding in tucked position. Two hypotheses were tested: (H1) Run times are affected by forward or backward leaning. (H2) Run times are affected by edging of the skis. Four professional ski testers were recruited, who conducted a total of 68 runs of straight gliding. Execution of the tasks was documented by video recordings and by measuring the force application point on the skis of one tester. The findings of this study support (H2) but not (H1). There are indications that the increased run times for edging are caused by increased ski-snow friction. From a performance point of view, it seems beneficial for ski racers to minimize edging in the gliding sections of a race.